Factors affecting career turnover intention after graduation among nursing students: A cross-sectional study in Central Vietnam - Tran Thi Thu Ha; Luu Thi Thuy; Do Thi Hoai Thanh (Tehran University of Medical Sciences, 2023)
Background & Aim: Turnover intention can predict the actual turnover behavior of nurses. Previous studies identified a variety of factors influencing nurses' turnover intention. However, few studies investigate nursing students' career turnover intention. This study aimed to examine turnover intention and associated factors among nursing students in Central Vietnam. Methods & Materials: A cross-sectional study was implemented among 425 nursing students recruited through a multistage sampling technique from April to May 2022. Data were collected using a questionnaire including demographic characteristics, fear of COVID-19, perceived academic stress, and turnover intention. Descriptive statistics were used to describe demographic characteristics and study variables. Independent t-test, one-way analysis of variance, and Pearson's correlation coefficients were computed to examine the association between variables. Results: Approximately one-third (32.5%) of the respondents will look for jobs without patient contact, 32.2% would not study nursing if given a choice, and 31.1% often think of not staying in the nursing profession. The sum scores of turnover intention ranged from 3 to 15 with a mean of 9.19 (SD= 2.49). The turnover intention was associated with the year of study, the reason to study nursing, and preparation for nursing school (p<.05). Perceived academic stress had a moderate correlation with turnover intention (r= -.325, p<.05). In contrast, the association between fear of COVID-19 and turnover intention was not significant. Conclusion: A considerable number of nursing students had turnover intention upon graduation. Factors affecting turnover intention should be considered to retain students in educational programs and avoid a future nursing shortage.